Edukasi Tanggap Darurat Pada Santri Pondok Pesantren X di Pamekasan - Wibisono, Fadeli; Rhomadhoni, Muslikha; Arrochman, Muhammad; Wahyudi , Muhammad; Ayu, Friska (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The X Islamic Boarding School, Pamekasan Regency, is almost a century old and is prone to accidents or emergencies, such as earthquakes and fires. Meanwhile, after direct observation, it turned out that Islamic boarding school X had not implemented an emergency response system. With so many students living and the administrators of the pesantren numbering in the hundreds, it is necessary to have preparations in case of an emergency. In this earthquake and fire emergency response activity, education will be carried out in the form of material provision on emergency response knowledge in the form of how to deal with an earthquake and fire hazard. The students were given a pre test before carrying out socialization and given a post test after being educated about earthquake and fire emergency response After the socialization, evacuation routes and assembly point boards were installed. This is a form of implementation in the field of Occupational Safety and Health (OSH) at the X Islamic Boarding School, Pamekasan Regency. By socializing and installing evacuation routes and assembly point boards, the students will know what emergency response means.